A Coldwater warm hearts Christmas [large type] - Eddings, Lexi (Eddings, Lexi. Coldwater series., 2018)
"High school English teacher Angie Holloway has been in this little Ozark hamlet for a few years, but she still feels like an outsider. And with no family of her own and single to boot, she's rusty when it comes to opening her heart. Nevertheless, she's been drafted to direct the annual Christmas pageant--whether she likes it or not. As for her assistant, that job's been handed to Seth Parker. He may be smoking hot, but the brawny construction engineer is definitely not her type. After all, she loves literature, he "reads" blueprints . . . While Angie tries to put a new spin on the show, and Seth tries to tolerate her correcting his grammar, they both resist the locals who insist on pushing them together. But when Seth finds her copy of Jane Austen's Sense and Sensibility--marked up with her revealing comments--he can't resist trying to romance her using his newfound knowledge. And Angie is surprised to find that this big, handsome lug can read her like a storybook hero."--